Factors Affecting Student Financial Behavior in Indonesia - Alexandro, Rinto (American Journal of Social Sciences and Humanities, 2019)
Financial education is expected to provide with an understanding of the importance of economic values to students economic behavior. This research is motivated by the low economic behavior of students, especially in financial management, such as a consumptive lifestyle without planning, borrowing high money without being able to pay it and other negative economic behavior. The purpose of this study was to determine the factors that influence the economic behavior of economic education college students in Palangka Raya, Central Kalimantan, Indonesia. The scientific method used for this research is quantitative. The population of this research is all coleege students of economic education in Palangka Raya who are familiar with the internet, because the research instruments are distributed to respondents through Google form. The sample is ten times the number of indicators in this case totaling 150 college students. To analyze the fix or not the model used F regression test. To determine the significance of the t test used, and to determine the contribution of independent variables to the dependent used the R square test. Based on the results of data analysis, it is concluded that there is a positive and significant influence between economic education and economic literacy on economic behavior both partially and simultaneously. Economic education variables make a greater contribution to economic behavior. Economic education and economic literacy are factors that contribute to economic behavior by providing an understanding of the importance of knowing the benefits and financial risks that college students do.